Adultery as a Complaint Offense in Overcoming Free Sex Behavior - Muhammad Topan (Scholar Center, 2023)
Globalization has a global meaning which is likened to freedom. Many foreign cultures have entered, even though these cultures are not in accordance with our Eastern culture. For example, the culture of free sex behavior that is widespread in Western culture is not to our culture and is contrary to the foundation of our country, Pancasila. Indonesia has six officially recognized religions, namely Islam, Protestant Christianity, Catholic Christianity, Hinduism, Buddhism, and Confucianism. The majority of official religions in Indonesia give the view that free sex is a deviant behavior. The opening of the 1945 Constitution in the third paragraph states that it is the grace of God Almighty and so on. That is, this view has juridical consequences for all laws and regulations which must refer to and originate from theological values, namely the value of Belief in the One and Only God. With the expansion of the offense of adultery in the new Criminal Code that